THE ROLE OF COMMUNITY FOR LOCAL DEVELOPMENT: A RESEARCH AGENDA - Khanh Hung DOAN (USV Annals of Economics and Public Administration, 2022)
Currently, local development plays an important role in the sustainable development of the country and is the driving force to ensure social stability. Many studies show that local development is influenced by different factors. Therefore, identifying the factors that affect local development is essential. Among the factors that affect local development, the community is identified as having a strong influence and bringing many benefits to local development in many different aspects. The goal of the paper is to determine the relationship between the community and local development using a systematic theoretical research method. The author analyzed the data collected through the Scopus database and a theoretical study based on the available research literature. The research results from the review of the literature indicate that the community and local development have a close relationship. Furthermore, the community plays an important role in sustainable local development according to many different criteria. Communities influence local development in the terms of the development of the economic, poverty alleviation, and in the terms of sustainability in the use of local resources, improving the well-being of individuals, protecting the environment and landscape, etc. The presented results contribute to promoting research on the relationship between community and local development.